Hands-on Python deep learning for web a comprehensive guide to integrating neural network architectures to bring smart automation for web - Singh, Anubhav (Packt Publishing, 2020)
This book will help you successfully implement deep learning in Python to create smart web applications from scratch. You will learn how deep learning can transform a simple web app into a smart, business-friendly product. You will also develop neural networks using open-source libraries and also integrate them with different web stack front-ends.